Stimulus Kultivasi pada Media Sosial dalam Mempengaruhi Kecenderungan Komunikasi Generasi Z - Aldy; Kholil, Syukur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study aims to analyze the influence of cultivation stimulus from social media on the communication tendencies of Generation Z. This generation grows up in the digital age with intensive exposure to social media content, which affects the way they interact and express themselves. The research method used is a qualitative approach with literature studies and in- depth interviews as data collection techniques. The literature study examined the theory of cultivation and the influence of social media, while in-depth interviews were conducted with members of Generation Z to gain an empirical perspective on their communication patterns. The results of the study show that the cultivation stimulus of social media, especially the content delivered by influencers, has a significant impact on shaping communication preferences. Generation Z is more likely to use visual symbols such as emojis and GIFs in digital communication, which shows an adaptation to the interactive features of social media platforms. In addition, it was found that social media facilitates active participation in social and political discussions, but also causes an echo chamber phenomenon that reinforces similar views. However, a high reliance on social media for social validation poses mental health risks, such as anxiety and depression. The study concludes that while social media provides opportunities for Generation Z to develop more expressive and socially engaged communication, good digital literacy is needed to mitigate any negative impacts that may arise. With a better understanding of the influence of cultivation stimulus, Generation Z can make wise and effective use of social media.